Maternal Exposure Results in Long-Term Deoxynivalenol Persistence in Piglets’ Plasma and Modulates the Immune System - Štěpánová, Hana (Toxins (Basel), 2020)
Deoxynivalenol (DON)-contaminated feed represents a serious problem for pigs due to their high sensitivity to its toxicological effects. The aim of the present study was to evaluate the impact of intrauterine DON exposure on the immune system of piglets. Pure DON was intravenously administered to sows at the end of gestation (during the last 2–3 days of gestation, one dose of 300 µg per day). The plasma concentration of DON was analyzed using liquid chromatography combined with high-resolution Orbitrap-based mass spectrometry (LC–MS/MS (HR)) and selected immune parameters were monitored six times in piglets from birth to 18 weeks. DON was found in the plasma of 90% of newborn piglets at a mean concentration of 6.28 ng/mL and subsequently, at one, three, and seven weeks after birth with decreasing concentrations. Trace amounts were still present in the plasma 14 weeks after birth. Flow cytometry revealed a significant impact of DON on T lymphocyte subpopulations during the early postnatal period. Lower percentages of regulatory T cells, T helper lymphocytes, and their double positive CD4+CD8+ subset were followed by increased percentages of cytotoxic T lymphocytes and γδ T cells. The capacity to produce pro-inflammatory cytokines was also significantly lower after intrauterine DON exposure. In conclusion, this study revealed a long-term persistence of DON in the plasma of the piglets as a consequence of short-term intrauterine exposure, leading to altered immune parameters.